Propriedades de medida e viabilidade dos equipamentos de diagnóstico elétrico sensorial não invasivo em indivíduos com desordens neurológicas: uma revisão sistemática - Fernandes, Caroline Nunes Pinto (2022)
INTRODUCTION: The loss of sensory function corroborates motor deficits and functional limitations in individuals with neurological health conditions. The sensory threshold (LS) is a considerable measure for the study of sensory pathways. SL is characterized by the lowest amount of detectable energy, with different electrical frequencies stimulating fibers of varying calibers and causing different per ceptual sensations. Thus, the ability to assess the sensory systems, through sinusoidal currents of different frequencies, by means of non invasive sensory electrical diagnostic equipment, must be present in the clinical decision making process of professi onals. OBJECTIVE : To summarize the measurement properties and clinical feasibility of non invasive sensory electrical diagnostic equipment in individuals with neurological health conditions and to determine the methodological quality of the studies and mea surement properties. METHODOLOGY : Systematic review of studies that investigated the measurement properties of non invasive sensory electrical diagnostic equipment in adult subjects (> 18 years old) with neurological health conditions of central or periphe ral etiology, which followed the PRISMA P, PROSPERO: CRD42020201819. The databases consulted were: MEDLINE, EMBASE, CINAHL, SCOPUS and WEB of SCIENCE. Manual searches in the references of included studies or articles relevant to the research were also perf ormed. The evaluation of the methodological quality of the studies was based on the COSMIN, for evaluating the quality of the measurement properties, the criteria proposed by Terwee et al., (2007) and the information on the clinical feasibility were extrac ted from the studies. RESULTS : We identified 856 articles (104 were duplicates) and after initial selection, 9 articles were potentially eligible, with only 8 articles selected after reading the full text. The methodological quality of the included studies ranged from ''Adequate'' to ''Doubtful'', according to COSMIN. Based on the criteria of Terwee et al., 2007, five studies were classified as indeterminate (?): the five studies on construct validity (hypothesis test). A Sufficient Rating (+) was identifie d in the four studies that investigated reliability. Insufficient data on clinical feasibility were found. Although none of the equipment investigated in terms of its measuring properties has shown strong evidence for the robustness of its properties, we h ighlight 3 potentially more suitable equipment, which evaluated: Pain tolerability and sensitization in a population with chronic low back pain with radicular neuropathic characteristics ; the electrical perceptual threshold in patients with chronic incomp lete cervical spinal cord injury and the current perception threshold in diabetic patients with neuropathy. CONCLUSION : The present systematic review highlights the paucity of studies that have investigated the measurement properties of non invasive sensor y electrical diagnostic equipment in individuals with neurological health conditions. Important measurement properties, such as construct validity, need to be better addressed by planned studies. More studies of high methodological quality on sensory elect rical diagnostic equipment are needed to help health professionals choose such a measurement tool.